2019
DOI: 10.3390/pathogens8040204
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Resistance, and Diversity of Salmonella along the Pig Production Chain in Southern Brazil

Abstract: Control of Salmonella spp. in food production chains is very important to ensure safe foods and minimize the risks of foodborne disease occurrence. This study aimed to identify the prevalence and main contamination sources of Salmonella spp. in a pig production chain in southern Brazil. Six lots of piglets produced at different farms were tracked until their slaughter, and samples were subjected to Salmonella spp. detection. The obtained isolates were serotyped, subjected to antimicrobial resistance testing, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
4
7
0
Order By: Relevance
“…Additionally, the combination of the PFGE profiles and the serological results showed that different serovars shared the same PFGE profile (subtype) and that the isolates of each serovar presented more than one subtype divided into different clusters, which demonstrates that PFGE is unable to discriminate Salmonella serovars. These results are in agreement with those reported in previous studies [50][51][52]. Moreover, these findings suggest the presence of different sources of contamination, which are in line with previous studies [51,53].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, the combination of the PFGE profiles and the serological results showed that different serovars shared the same PFGE profile (subtype) and that the isolates of each serovar presented more than one subtype divided into different clusters, which demonstrates that PFGE is unable to discriminate Salmonella serovars. These results are in agreement with those reported in previous studies [50][51][52]. Moreover, these findings suggest the presence of different sources of contamination, which are in line with previous studies [51,53].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with those reported in previous studies [50][51][52]. Moreover, these findings suggest the presence of different sources of contamination, which are in line with previous studies [51,53]. In addition, our results showed that the differences in the PFGE patterns cannot be linked to the difference in antimicrobial-resistant genotypes among the same serovar.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, genes codifying extended spectrum beta-lactamases (ESBL) or carbapenemases as well as resistance to macrolides have been emerged as a particular concern (WHO 2018b). In this regard, all tested strains were susceptible to these antimicrobial groups in agreement with other reports of very low frequency or absence of resistance to these drugs in Salmonella originated from the Brazilian swine production chain (Bersot et al 2019, Monte et al 2019). On the contrary, antimicrobials such as ampicillin, tetracycline and nalidixic acid have been often reported among the group of highest levels of resistance in food borne pathogens (Lopes et al 2015, Almeida et al 2018, Monte et al 2019.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of MDR Salmonella strains in foods, such as poultry meat, is a major concern, considering their extremely resistant phenotypes and several transferable determinants (resistance genes to plasmid-and integron-mediated antibiotics) [39]. Bersot et al [123] evaluated the antimicrobial resistance of Salmonella in the pork production chain in Southern Brazil and reported a high incidence of MDR strains. In addition, the authors pointed out the need for greater monitoring of antimicrobial resistance in the pork production chain and the possibility of these strains to be transmitted to humans.…”
Section: Mdr Biofilms In the Food Production Chainmentioning
confidence: 99%